Pendekatan Desain Partisipatif dalam Pengembangan Identitas Kawasan melalui Mural pada Kampung Kreatif Bojongmalaka - ASM Atamtajani; Fajar Sadika (Cahaya Pengabdian, 2026)
Public spaces play a strategic role in strengthening community identity and encouraging active participation in the development of creative villages. Kampung Kreatif Bojongmalaka, Bandung Regency, possesses considerable local potential; however, its environmental identity had not yet been visually represented through public facilities reflecting the community's collective values. This community service program aimed to strengthen the area's identity by implementing a participatory design approach in developing community-based murals. The program employed participatory design methods consisting of stakeholder identification, field observation, focus group discussions, collaborative concept development, mural sketch competitions, design refinement, and mural implementation involving local residents. The results demonstrate that participatory design successfully increased community engagement throughout the planning and implementation stages while fostering a stronger sense of ownership toward public spaces. The resulting murals visually represent local characteristics, including volleyball, Jaipongan dance, and the local footwear industry, which were collectively identified as symbols of the village's identity. In addition to improving the visual quality of the neighborhood, the murals have become a medium for expressing local identity, strengthening social interaction, and supporting the sustainability of Kampung Kreatif Bojongmalaka as a community-based creative village. This program confirms that participatory design can serve not only as a collaborative design method but also as an effective empowerment strategy for developing meaningful public spaces through active community involvement.